Relationship between Citizen-Eyewitness Images and Audience Engagement with News. (14th September 2022) - Kim, Jisu; Huh, Jisu; Rath, Bhavtosh; Salecha, Aadesh; Srivastava, Jaideep
ABSTRACT: This study explores the extent to which U.S. newspaper organizations incorporate images captured by private citizens into their news articles as an audience engagement strategy, and examines the relationship between the extent to which citizen-eyewitness images are incorporated in the news and audience news engagement. By conducting a machine-coding analysis of news images and analyzing user behavioral data on Twitter, this study found that U.S. newspapers tended to incorporate a rather small number of citizen-eyewitness images in their news reports. The findings also revealed that the extent to which a news organization incorporated citizen-eyewitness images in its news articles was positively related to audience engagement with its news.